Tumour-derived PGD2 and NKp30-B7H6 engagement drives an immunosuppressive ILC2-MDSC axis - Sara Trabanelli (Nature Portfolio, 2017)
Group 2 innate lymphoid cells (ILC2s) modulate inflammatory and allergic responses, but their function in cancer immunity is still unclear. Here the authors show that, in acute promyelocytic leukaemia, tumour-activated ILC2s secrete IL-13 to induce myeloid-derived suppressor cells and support tumour growth.